Corporate Criminal Liability In Oil and Gas Sector Crimes In Indonesia - Eben Heser Tarigan; Yasmirah Mandasari Saragih (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2024)
This research addresses the issue of corporate criminal liability in crimes occurring within Indonesia’s oil and gas sector. In modern criminal law, corporations are increasingly recognized as legal entities capable of bearing criminal responsibility, particularly in cases related to economic offenses, environmental violations, and corruption. The oil and gas sector, being one of the most strategic and high-value industries, is highly susceptible to legal violations by corporate entities. Given the significant role this sector plays in the national economy, the accountability of corporations in this field is of utmost importance to ensure proper legal oversight and prevent harmful practices. The research employs a normative juridical approach, utilizing statutory, conceptual, and case study methods to examine how corporate criminal liability is applied in the oil and gas industry in Indonesia. The findings reveal that the regulation of corporate criminal liability in the oil and gas sector remains underdeveloped, as it is not explicitly addressed in the Oil and Gas Law. This lack of clear and specific regulation creates gaps in law enforcement, leaving corporations with opportunities to evade full accountability for crimes they commit. While existing legal frameworks such as the Anti-Corruption Law, Environmental Law, and PERMA No. 13/2016 provide a foundation for criminalizing corporations in cases of wrongdoing, the practical implementation of these regulations within the oil and gas sector has proven to be insufficient. Several factors contribute to the weak enforcement of corporate criminal liability. First, there are technical challenges in proving corporate involvement in criminal acts, as the actions of a corporation are often difficult to attribute to specific individuals. Second, the capacity of law enforcement agencies to effectively investigate and prosecute corporate crimes is limited, compounded by a lack of expertise and resources.